2021
DOI: 10.1017/s136898002100402x
|View full text |Cite
|
Sign up to set email alerts
|

Association between the socio-economic status of households and a more sustainable diet

Abstract: Objective: A sustainable diet is an affordable diet with low environmental impact, high food security, and sufficient healthiness. The present study aimed to assess the correlation between the socioeconomic status of households and a sustainable diet. Design: The food basket and socioeconomic data of Iranian households were evaluated during 2016-2018. The households were classified based on the sustainability of their diet by determining the dietary carbon footprint, dietary water footpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
1
6
0
1
Order By: Relevance
“…This is consistent with data from Mexico City [ 54 ] that suggests that the traditional dietary pattern (consisting primarily of maize and beans) is associated with lower socioeconomic status. These results also coincide with studies conducted in other countries where higher socioeconomic status is associated with higher consumption of calories and animal-based foods [ 55 , 56 ]. A study of 2006–2016 data has suggested that Mexican adults with lower socioeconomic status have a better quality diet than those with higher socioeconomic status [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with data from Mexico City [ 54 ] that suggests that the traditional dietary pattern (consisting primarily of maize and beans) is associated with lower socioeconomic status. These results also coincide with studies conducted in other countries where higher socioeconomic status is associated with higher consumption of calories and animal-based foods [ 55 , 56 ]. A study of 2006–2016 data has suggested that Mexican adults with lower socioeconomic status have a better quality diet than those with higher socioeconomic status [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…29 Within high-income countries, individuals' dietary environmental impact is higher among men, 30,31 and increases hand in hand with socioeconomic status and incomes. 27,32 Food insecurity and hunger are even experienced among people with the lowest incomes in high-income countries. 33 Thus, individuals from upper socioeconomic level in high income countries, especially men, should be targeted first if we are to achieve significant reductions in dietrelated environmental impact and a fair food system as soon as possible.…”
Section: Promoting Individual Eating Behaviour Change: Why For Whom A...mentioning
confidence: 99%
“…Among those meeting inclusion criteria, participants will be classified in three groups according to their subjective socio-economical level. The reason behind this stratification is that socio-economic level is a major determinant for food choices and individual dietary carbon footprint [26,27]. Additionally, deprived populations might also benefit less from interventions delivered via digital or mobile means; it is thus necessary to include social inequality indicators such as socio-economic status in the evaluation of interventions to assess their potential differential impact [28,29].…”
Section: Participantsmentioning
confidence: 99%